Influence of biochar derived from Cd polluted silkworm excrement on the phytoavailability of Cd in a paddy soil and its accumulation in mulberry - Yongbing Jiang; Xiyun Yang; Shimeng Jiang; Hui Cao; Ming Wang; Zhangbao Li (Ecotoxicology and Environmental Safety)
Developing sericulture industry is a promising model for the utilization of soils heavily contaminated with cadmium (Cd), but the management of polluted silkworm excrement (SE) becomes challenging. This study aimed to evaluate the effects of the SE biochar (SB) with Cd (SB-Cd) and without Cd (SB-Cd free) on the chemical properties of paddy soil, the mulberry leaf quality and the accumulation of Cd in mulberry. The soil incubation experiments showed that the two SBs all raised the acidic soil pH (20.24 %∼49.97 %) significantly (P < 0.05) with the increasing SB addition rates. The two SBs increased the soil cation exchange capacity (CEC) and played an essential role in reducing the phytoavailability of Cd. The pot experiment elucidated the two SBs all promoted the growth of mulberry, increased the crude protein content and the chlorophyll content, reduced the total sugar content in leaves. The Cd concentrations in root, stem, leaf were decreased with the increase of SB respectively, but no significant differences were found between the same additions of SB-Cd free and SB-Cd. The use of SB-Cd for remediation of the Cd polluted soils could be a reasonable method to address the Cd polluted SE.